Guidelines for Building Confidence in Crime Scene Inspections by Forensic Officers in Phetchabun Province - Kundiloknattawasa, Netithorn; Kulnides, Narong; Chokstathapornchai, Chuchart (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This objective of this research was to: to propose guidelines for building confidence in crime scene inspection by forensic officers in Phetchabun Province. The population used as an important source of information this time is the deputy director (investigation) of the police station in Phetchabun Province who was assigned to be the head of the investigation, totaling 18 persons, who were purposively selected. The research instrument used was in-depth interviews and content analysis. The research results found that guidelines for building confidence in crime scene inspection by forensic officers in Phetchabun Province 1) Knowledge and skills, consisting of: 1.1) scientists who inspect crime scenes must be knowledgeable and skilled; 1.2) having skills and expertise in inspecting crime scenes; 1.3) quick wit in inspecting crime scenes; 1.4) give advice to investigators to observe and control entry into the crime scene without destroying or contaminating evidence, 2) Ethics of forensic investigators, consisting of: 2.1) inspecting crime scenes quickly; 2.2) having good interpersonal skills with investigators; 2.3) not demanding or accepting property or benefits; 2.4) performing duties with honesty and integrity; 2.5) having patience in inspecting crime scenes; 2.6) traveling to inspect crime scenes immediately without delay; 2.7) performing duties willingly. 3) Behavior in performing duties includes 3.1) entering to inspect the scene of the incident without delay 3.2) a good-natured person 3.3) behaving appropriately and showing respect for each other 3.4) enthusiastic in performing duties 3.5) dressing neatly and appropriately for performing duties 4) Systematicity in performing duties includes 4.1) professional 4.2) performing duties according to the specified standards and procedures 4.3) having a time frame for performing duties and performing duties properly and completing them according to the specified procedures 4.4) having the readiness of materials, equipment and tools for performing duties 4.5) being able to perform duties immediately when requested or notified of an incident.